THE INFLUENCE OF COMMUNICATIVE LANGUAGE TEACHING APPROACH AND SPEAKING HABIT TOWARDS THE EIGHTH GRADE STUDENT’S SPEAKING ABILITY (English Community Journal, 2023)
The aim of this study was to know whether or not a significant influence in speaking ability after the students with positive and negative speaking habit being taught by Communicative Language Teaching Approach, identifying the significant intraction effect of Communicative Language Teaching Approach and speaking habits on student's speaking ability. In this study, the writer used two stage random sampling. The data were collected by using pretest and posttest. The data were analyzed by using Paired Sample t-test, Independent Sample t-test and Two-Way Anova. The finding of this study is the results of speaking ability between students with positive is higher than students with negative speaking habit being taught by Communicative Language Teaching Approach. It can be concluded that Communicative Language Teaching Approach can improve student’s speaking Ability.